Agreement between force and deceleration measures during backward somersault landings - Bradshaw, E. J.; Grech, K.; Joseph, C. W. J.; Calton, M.; Hume, P. A. (Sports Biomechanics, 2020)
This study examined the agreement between force platform and inertial measurement unit (IMU) measures of backward somersault landings. Seven female gymnasts performed three trials, taking off from a 90 cm vaulting box and using competition landing technique. Two force platforms (1000 Hz) covered with a 6.4 cm thick carpeted landing surface measured the ground reaction forces. One inertial measurement unit (500 Hz) fixed on the second thoracic vertebra measured peak resultant deceleration of the gymnast. Measurement agreement between vertical and resultant peak force measures, and resultant peak force and peak deceleration was assessed using mean differences, Pearson's correlation, and Cohen's effect size (ES) statistics. There was perfect measurement agreement between vertical and resultant peak forces (R = 1.0, p < 0.001; ES = 0.005), but only moderate measurement agreement between resultant peak force and peak resultant deceleration (Mean Difference = -2.16%, R = 0.4, p = ns; ES = 0.121). Backward somersault landings can be assessed using either uni-axial or tri-axial force platforms to measure ground impact load/force, as the landing movements are almost purely vertical. However, force measures are not the same as peak resultant decelerations from IMUs which give an indication of impact shock. Landing load/shock measures are potentially important for injury prevention.